The cat who sang for the birds - Braun, Lilian Jackson (Putnam, 1998)
Newspaperman Jim Qwilleran and his two cats, Koko and Yum Yum, investigate a suspicious fire which killed a woman in her nineties. The 20th volume in the series, the novel introduces a new character, a swearing parrot.